2021
DOI: 10.3390/su132212501
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Impacts of Hybrid Campus and Autonomous Electric Vehicles as GHG Mitigation Strategies: A Case Study for a Mid-Size Canadian Post-Secondary School

Abstract: This paper presents how a post-secondary institution like University of British Columbia’s Okanagan (UBCO) campus can reduce its carbon footprint and be aligned with the government’s target through promoting virtual campus and autonomous electric vehicles (AEVs). Different virtual campus scenarios are developed: online classes only, working-from-home only, and a hybrid of both. In the case of AEVs, alternative penetration rates for levels 2 and 5 are considered. A total of 50 scenarios are tested using a sub-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Many researchers expect that introducing autonomous vehicles as next-generation driving systems will remarkably impact traffic capacity and safety [1][2][3]. Furthermore, AVs are believed to have outstanding advantages in other important parameters such as reducing energy intensity, fuel consumption and emissions, travel time, and congestion [4][5][6]. Therefore, the desire to use this new form of transport has become a globally spread fact, especially in modern societies.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers expect that introducing autonomous vehicles as next-generation driving systems will remarkably impact traffic capacity and safety [1][2][3]. Furthermore, AVs are believed to have outstanding advantages in other important parameters such as reducing energy intensity, fuel consumption and emissions, travel time, and congestion [4][5][6]. Therefore, the desire to use this new form of transport has become a globally spread fact, especially in modern societies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in terms of energy consumption, using autonomous vehicles fleet provides significant advantages over identical internal combustion engine vehicles by up to 67%. Another study explored the use of autonomous vehicles within university campuses and showed that they could reduce greenhouse gas emissions by 36% at a 40% penetration level 19 . As the penetration level increases, there will be a greater reduction in greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%